Book Review. Feeling Gender: A Generational and Psychological Approach - Rudy Rudy (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
As one of the phenomenal issues in the world, gender has always been an unfinished argument among experts, researchers, and academicians. With the growth of science and technology and the development of media in the 20th century, there have been many changes in perceiving gender. Topic on gender which was not widely discussed in academic forum has become an important topic nowadays. Studies and researches on gender have been in great progress since 1990s when more and more experts such as Judith Butler, Donna Haraway, etc. began to publish their writing on gender and sexuality. People started learning more about this issue.A common thing that people may understand is that there are biological and social factor which give a significant impact to gender categorizations (Fagot et al, 1997: 2). However, gender issues remain arguable topics from time to time. Era changes and one generation is replaced by another younger generations. From this condition, Harriet Bjerrum Nielsen, the professor at the Centre for Gender Research at the University of Oslo, Norway has shown her serious concern on how feelings of gender can change from one generation to another by observing the how men and women from some generations feel about their relationships toward their parents in order to reveal what gender really is to them. Therefore, this study incorporates a generational and psychological approach for analysis.